The cobalamin-binding protein in zebrafish is an intermediate between the three cobalamin-binding proteins in human. - Eva Greibe; Sergey Fedosov; Ebba Nexo (PLoS ONE, 2012)
In humans, three soluble extracellular cobalamin-binding proteins; transcobalamin (TC), intrinsic factor (IF), and haptocorrin (HC), are involved in the uptake and transport of cobalamin. In this study, we investigate a cobalamin-binding protein from zebrafish (Danio rerio) and summarize current knowledge concerning the phylogenetic evolution of kindred proteins. We identified a cobalamin binding capacity in zebrafish protein extracts (8.2 pmol/fish) and ambient water (13.5 pmol/fish) associated with a single protein. The protein showed resistance toward degradation by trypsin and chymotrypsin (like human IF, but unlike human HC and TC). The cobalamin analogue, cobinamide, bound weaker to the zebrafish cobalamin binder than to human HC, but stronger than to human TC and IF. Affinity for another analogue, adenosyl-pseudo-cobalamin was low compared with human HC and TC, but high compared with human IF. The absorbance spectrum of the purified protein in complex with hydroxo-cobalamin resembled those of human HC and IF, but not TC. We searched available databases to further explore the phylogenies of the three cobalamin-binding proteins in higher vertebrates. Apparently, TC-like proteins are the oldest evolutionary derivatives followed by IF and HC (the latter being present only in reptiles and most but not all mammals). Our findings suggest that the only cobalamin-binding protein in zebrafish is an intermediate between the three human cobalamin binders. These findings support the hypothesis about a common ancestral gene for all cobalamin-binding proteins in higher vertebrates.